PARADIPLOMATIC APPROACHES TO THE AMAZON TRIPLE BORDER: BRAZIL, COLOMBIA AND PERU - Laura de Nazaré Rocha Andrade; Maria Luiza Machado Granziera (Revista Tempo do Mundo, 2022)
Global dynamics have changed as a result of globalization. And due to the emergence of new demands, whether they were economic, social or environmental, it enabled new actors to be part of these dynamics. The inclusion of these new state and non-state actors was due to the emergence of unexplored or little explored gaps by the state power, which still has a rigid structure and far from meeting the expectations and needs of these new dynamics. Important factors such as the physical distance from decision-making centers, and the social and economic issues that need rapid answers contribute to the strengthening of paradiplomatic approaches, in addition to the rigidity of States. These new relationships are reflected in regional and cross-border integration as the case of the paradiplomatic approach on the borders of Brazil, Peru, and Colombia, which was driven by the intensification of environmental problems leading to the spatial cutout, due to its insulating characteristic. This article was based on bibliographic research, books, theses, dissertations, and scientific articles on this subject, aiming to verify whether is cooperation and cross-border integration is observed.